Interferon-γ/Interleukin-27 Axis Induces Programmed Death Ligand 1 Expression in Monocyte-Derived Dendritic Cells and Restores Immune Tolerance in Central Nervous System Autoimmunity - Casella, Giacomo; Rasouli, Javad; Thome, Rodolfo; Descamps, Hélène C.; Vattikonda, Asrita; Ishikawa, Larissa; Boehm, Alexandra; Hwang, Daniel; Zhang, Weifeng; Xiao, Dan; Park, Jeongho; Zhang, Guang-Xian; et al. (Frontiers in Immunology, 2020)
Antigen (Ag)-specific tolerance induction by intravenous (i. v.) injection of high-dose auto-Ags has been explored for therapy of autoimmune diseases, including multiple sclerosis (MS). It is thought that the advantage of such Ag-specific therapy over non-specific immunomodulatory treatments would be selective suppression of a pathogenic immune response without impairing systemic immunity, thus avoiding adverse effects of immunosuppression. Auto-Ag i.v. tolerance induction has been extensively studied in experimental autoimmune encephalomyelitis (EAE), an animal model of MS, and limited clinical trials demonstrated that it is safe and beneficial to a subset of MS patients. Nonetheless, the mechanisms of i.v. tolerance induction are incompletely understood, hampering the development of better approaches and their clinical application. Here, we describe a pathway whereby auto-Ag i.v. injected into mice with ongoing clinical EAE induces interferon-gamma (IFN-γ) secretion by auto-Ag-specific CD4+ T cells, triggering interleukin (IL)-27 production by conventional dendritic cells type 1 (cDC1). IL-27 then, via signal transducer and activator of transcription 3 activation, induces programmed death ligand 1 (PD-L1) expression by monocyte-derived dendritic cells (moDCs) in the central nervous system of mice with EAE. PD-L1 interaction with programmed cell death protein 1 on pathogenic CD4+ T cells leads to their apoptosis/anergy, resulting in disease amelioration. These findings identify a key role of the IFN-γ/IL-27/PD-L1 axis, involving T cells/cDC1/moDCs in the induction of i.v. tolerance.